Penguatan Kapasitas Kelompok Wanita Tani (KWT) Desa Karangturi Melalui Program Rumah Masyarakat Tani - Anggun Melvana Audria; Adifa Istiqomah; Anggun Tri Hapsari; Eksa Rusdiyana; Utami, Bekti Wahyu (Edujavare Publishing, 2024)
This community service activity aims to increase the capacity of the Karangturi Village KWT through the Farmer Community House (RUMAT) program. The aim of this service is to reactivate the Karangturi Village KWT with a number of educational activities to re-stimulate the organizational spirit of women farmers. The service method uses Participatory Rural Appraisal (PRA) through identification of problems and needs, outreach, and education to increase knowledge and training. Based on the results of the service that has been carried out, the impact of the activities can be obtained in the form of (1) reactivation of KWT which has been passive, (2) construction of houses for farming communities, and training in organic waste management, practices, and nurseries. Evaluation of activities showed an increase in participants' knowledge about the importance of agricultural institutions for women and increased skills in seeding techniques and organic waste management. So, it can be concluded that we have succeeded in strengthening the Women Farmers Group (KWT) institution in Karangturi Village, in order to support agricultural development, educational facilities and development of the agricultural sector.